Model Quantum Learning Pendidikan Agama Islam - ‘Ulyan, Mohammad (Educreative : Jurnal Pendidikan Kreativitas Anak, 2019)
Quantum learning is an active learning model, strategy, and approach that seeks toturn the interaction between teachers, students, and their environment into light.The light here is intended as a radiance as a result of positive interactions in learning.Therefore, in implementing this learning model, it is expected that there is anorchestration between context and content. It is certainly packed in a passionate, funand easy learning frame for students. With the principle of "bring their world intoour world, and deliver our world to their world" then the divide between teachersand students can be resolved. Through TANDUR philosophy, namely Grow, Natural,Name, Demonstration, Repeat, and Celebrate so as to increase student participation,spirit, interest and character of students.